The characterization and application of chip topside bonding materials for power modules packaging: a review. (August 2020) - Liu, Keming; Yang, Jinlong; Luo, Jian; Wang, Li; Huang, Quanquan; Chen, Fei
Abstract: Bonding material is one weak point in power modules packaging, and can limit the lifetime of power modules. Multiple bonding materials have been manufactured and applied in the power modules such as aluminum wire, copper wire, aluminum ribbon, copper ribbon, Al-clad-Cu wire, direct-bonding-lead. For bonded power modules packging, bonding ability, electrical and thermal conductivity, current carrying capacity, working reliability are the main applying properties of bonding materials. This paper demonstrates the characterization, failure mode & failure mechanism, life-time calculation model of the normal used bonding materials and estimates the developing tendency.